'Don't Call Me White': Fashioning Sami Zayn's Arabic and transnational identities. Issue 2 (1st September 2015) - Roberts, J. H.
Though mainstream professional wrestling depends on and benefits from anglo-normative, Western hegemony, contemporary wrestling also subverts and parodies it. One character who can be read as white, Sami Zayn, undermines this hegemony through subtly asserting his Arabic and transnational identities. In wrestling, a character's apparel functions as a metonym for the character, and with his tights Zayn counters mainstream Islamophobic discourse about Arabs post 9/11. Zayn's tights are decorated with many national flags, Arabic characters and Roman letters to show he possesses a complex identity influenced by not only his ethnic heritage (Syrian) and country of birth (Canada), but every country he has visited and the cultures within them. His popularity and success allow a space within World Wrestling Entertainment for non-white characters to perform identities not limited to caricatures of their ethnic and racial backgrounds.